DENTAL WEAR AND TOOTH LOSS IN MORBID OBESE PATIENTS AFTER BARIATRIC SURGERY - Fabiano Duarte AZNAR; Fabio D. AZNAR; José R. LAURIS; Elinton Adami CHAIM; Everton CAZZO; Silvia Helena de Carvalho SALES-PERES (ABCD: Arquivos Brasileiros de Cirurgia Digestiva, 2019)
ABSTRACT Background: Obesity and its surgical treatment have been related with oral diseases. Aim: To evaluate and compare dental wear and dental loss in eutrophic and morbidly obese patients submitted to Roux-en-Y gastric bypass. Method: Observational and analytical study with gender and age matching. The sample consisted of 240 patients, divided into four groups: eutrophic (GC=60), morbidly obese (GO=60), operated with up to 24 months (G24=60) and operated on for more than 36 months (G36=60). The following variables were analyzed: race, schooling, economic class, hypertension, diabetes, triglycerides, cholesterol, BMI, weight loss, waist-hip ratio, smoking, alcoholism, tooth loss and tooth wear. Results: GO presented lower economic class (p=0.012), hypertension (p<0.001), diabetes (p<0.001), cholesterol (p=0.001), BMI (p<0.001), waist-hip ratio (p<0.001) and percentage of weight loss percent (p<0.001) than groups G24 and G36. Dental wear was higher among the II and V sextants. Conclusion: Individuals submitted to Roux-en-Y gastric bypass, regardless of the surgery period, presented more dental wear on the incisal/occlusal surfaces, and the anterior teeth were the most affected. Dental wear was associated with age and number of missing teeth.